INCREASING STUDENTS' LEARNING MOTIVATION THROUGH INSTAGRAM MEDIA IN WRITING CAPTIONS AT SENIOR HIGH SCHOOL STUDENTS - Marlinda (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
The objective of this research is to figure out is there any increasing in students' motivation and learning outcomes in writing captions after learning using Instagram media. The data were collected by applying test and questionnaire. The subject of this research were 36 students from class XI-D2 whom the researcher followed their Instagram. The result of this research showed that the students’ writing caption ability was varied. In the pre-test, there were only 4 students who passed the completeness limit. After carrying out the cycle 1 post-test, students who achieved completeness increased to 27 students or 75% of the total number. The score results from the implementation of post-test cycle 2 showed an increase in 36 students who achieved completeness. To conclude, the students’ abilities in writing caption on Instagram are fairly good, even though there were elements need to be improved.